Involving the third sector in local service delivery in Bangladesh: Why and how? (Commonwealth Journal of Local Governance, 2015)
The rise of involuntary and non-government efforts to deliver services in Bangladesh has opened the way for local government units to involve many community and voluntary organisations (CVOs) and non-governmental organisations (NGOs)– collectively described as the ‘third sector’ – in delivering local services. This article attempts to set out how the third sector can be incorporated into the stream of local service delivery. It analyses the rationale behind the engagement of the third sector in this area. It also looks at suitable mechanisms to enable local government institutions (LGIs) and third sector organisations to meet community objectives seamlessly, transparently and fairly. During the last two decades or so, many third sector organisations have collaborated with public sector organisations including LGIs regardless of any specific long term strategies. To involve the third sector in local service delivery there should be some clear cut standard procedures, strategies including commissioning, partnership, competitive contracting and co-production. The article concludes that, given the current situation of LGIs in Bangladesh, only co-production is a suitable mechanism for incorporating the third sector into local service delivery.